The rage of innocence: how America criminalizes black youth - Henning, Kristin (Pantheon Books, 2021)
American Adolescence in Black and White -- Toy Guns, Cell Phones, and Parties: Criminalizing Black Adolescent Play -- Hoodies, Hip Hop, and Headwraps: Criminalizing Black Adolescent Culture -- Raising "Brutes" and "Jezebels": Criminalizing Black Adolescent Sexuality -- Policing Identity: The Politics of Adolescence and Black Identity Development -- Cops in School -- Contempt of Cop -- Policing by Proxy -- Policing as Trauma -- The Dehumanization of Black Youth: When the Children Aren't Children Anymore -- Things Fall Apart: Black Families in an Era of Mass Incarceration -- #BlackBoyJoy and #BlackGirlMagic: Adolescent Resilience and Reform.